Frequency of Gastroesophageal Reflux Disease in Chronic Obstructive Pulmonary Disease Patients - Iftikhar Ali Kakar, Abdul Baqi, Nasir Azim, Waqas Ahmad, Zeeshan Shaukat, Khalid Shahab, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: About 20% to 30% of the general population, especially in individuals with old age, suffers from gastroesophageal reflux disease. Association between gastroesophageal reflux disease and chronic obstructive pulmonary disease has been reported in numerous studies. Objective: To find out the frequency of gastroesophageal reflux disease in chronic obstructive pulmonary disease patients Methodology: This cross-sectional study was carried out at the department of Pulmonology, Fatima Jinnah Institute of Chest Diseases and Sheikh Khalifa Bin Zayyed Al Nahyan Medical Complex Quetta from December 2021 to May 2022. The inclusion criteria for our study were all the patients of either gender in age range 18 to 60 years diagnosed with COPD of any severity level. A proforma developed solely for this research was used to record all the data. All the collected data was analyzed by using SPSS version 23. Results: In our study, totally 180 patients were enrolled. There were 120 (66.67%) male participants and 60 (33.33%) female participants in our study. The overall frequency of gastro-esophageal reflux disease in COPD patients was 93 (51.67%). The frequency of gastro-esophageal reflux disease in mild, moderate severe and very severe COPD patients COPD patients was 4 (44.44%), 39 (48.15%), 38 (52.78%) and 12 (66.66%) respectively. Conclusion: Our study concludes that the frequency of gastroesophageal reflux disease is high in chronic obstructive pulmonary disease patients. Based on our results, every patient who presents with COPD should be screened for GERD. Keywords: Frequency, gastroesophageal reflux disease, chronic obstructive pulmonary disease